Upaya Peningkatan Kesejahteraan Petani dan Usaha Desa Melalui PT. Mitra Desa Pamarican sebagai Aktivitas Corporate Social Responsibility (CSR) PT. Bank Mandiri (Persero) Tbk. - Shandi Pratama (Program Studi Ilmu Kesejahteraan Sosial FISIP UNPAS, 2022)
In an effort to deal with population growth, it is necessary to have good food security from a country. How can a country have good food security if the agricultural industry sector alone does not have human resources and good use of technology? For this reason, it is necessary to have certain stakeholders who take part in efforts to improve the welfare of farmers in order to improve resources and ensure the sustainability of the agricultural industry sector. PT Bank Mandiri through its Corporate Social Responsibility activitiy, PT. Mitra Desa Pamarican play a role as stakeholders in efforts to improve the welfare of farmers and businesses in Pamarican Village, Ciamis Regency. This article will explain how the PT Mitra Desa Pamarican program has succeeded in improving the welfare of farmers and through increasing village-owned business activities, as well as improving the quality of agricultural products through the use of technology. This article uses a qualitative descriptive method through literature study using secondary data in obtaining the data. The purpose of this article is to explore structurally how the Corporate Social Responsibility program can provide benefits for both the company and the recipient community. Keywords: Welfare of farmers, agricultural industry, corporate social responsibility